Uneven response of microbial communities to intense dust deposition across the coastal transition zone off Mauritania - Pérez-Barrancos, Clàudia; Gelado-Caballero, María D.; Hernández-Hernández, Nauzet; Baños, Isabel; Gómez-Letona, Markel; Montero, María F.; Arrieta, Jesús M.; Arístegui, Javier (Frontiers in Marine Science, 2022)
The eastern North Atlantic region receives large Saharan dust deposition inputs, providing nutrients and trace metals to the surface waters. We assessed the effects of intense dust deposition on phytoplankton and bacteria cell abundances, metabolic activity, and community structure, along a surface productivity gradient in the Mauritanian-Senegalese upwelling system. Dust concentrations above 4 mg L-1 were added to triplicate microcosms in four bioassay experiments, each lasting three days, increasing nitrate, phosphate and, to a lesser extent, silicate seawater concentrations. Even though dust deposition enhanced both heterotrophic and photosynthetic activity, bacterial production responded faster and stronger than primary production, especially as oligotrophic conditions increased. Bacterial production rates in oligotrophic waters almost tripled one day after the enrichment. However, such favorable response could not be observed on the total organic carbon production until a lag phase of 2 days and whilst under moderate eutrophic conditions. Dust enrichment benefited the presence of certain planktonic groups over others according to their nutrient requirements. Indicator species analysis revealed that our dust-treated microcosms were consistently characterized by Raphid-pennate diatoms, as well as by Hyphomonas genus of Alphaproteobacteria and several species of Alteromonas Gammaproteobacteria. Yet, changes in microbial community structure and composition were primarily shaped by the starting conditions of each experiment. These findings indicate that increasing dust deposition events and the weakening of the Mauritanian-Senegalese upwelling system under climate change may result in a more heterotrophic system, particularly in oligotrophic waters, reducing its potential to function as an atmospheric carbon sink.